2018
DOI: 10.1111/ced.13793
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous features of Zika virus infection: a clinicopathological overview

Abstract: Summary Zika virus (ZIKV) is an emerging mosquito‐borne flavivirus transmitted mainly by Aedes species of mosquitos. Although the infection is usually mild and self‐limiting, it is emerging as a public health challenge in tropical and subtropical countries owing to its unprecedented pathogenicity and increased risk for fetal malformations and neurological symptoms. Cutaneous manifestations as for other mosquito‐borne viruses remain a hallmark of the disease. This article provides a detailed overview on ZIKV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
2
17
0
4
Order By: Relevance
“…First’s reports evaluating cell permissiveness demonstrated that ZIKV replicates at placental trophoblasts, endothelial cells, human skin fibroblast and neonatal keratinocytes (21, 35, 36). ZIKV also replicates and induce morphological alterations in human skin explants (35), that are consistent with skin lesions presented in many ZIKV-infected patients (37). After mosquito inoculation, skin cells (keratinocytes and dendritic cells) are the first target of ZIKV, followed by hematological dissemination.…”
Section: Discussionsupporting
confidence: 63%
“…First’s reports evaluating cell permissiveness demonstrated that ZIKV replicates at placental trophoblasts, endothelial cells, human skin fibroblast and neonatal keratinocytes (21, 35, 36). ZIKV also replicates and induce morphological alterations in human skin explants (35), that are consistent with skin lesions presented in many ZIKV-infected patients (37). After mosquito inoculation, skin cells (keratinocytes and dendritic cells) are the first target of ZIKV, followed by hematological dissemination.…”
Section: Discussionsupporting
confidence: 63%
“…Skin lesions ranging from morbilliform and exanthem like eruptions to erythroderma to confluent macular eruptions simulating chikungunya (Fig. 1f) have been reported 58 . Psoriasis is reported to be triggered after an acute Zika virus infection 59 …”
Section: Zika Virusmentioning
confidence: 99%
“…The mucosal lesions include conjunctivitis characterised by non‐purulent conjunctival hyperaemia. Oral mucosa may show aphthous and ulcerative lesions, while hyperaemia and petechial lesions over the hard palate have been described 58 …”
Section: Zika Virusmentioning
confidence: 99%
“…This is in contrast to the rash in dengue and Chikungunya, which usually appears after 4 days of clinical symptoms. [58] Other uncommon cutaneous features are as follows: subcutaneous hematomas, ecchymosis, petechiae, aphthous ulcers, and other ulcerative oral mucosal lesions. [58]…”
Section: Clinical Features and Differential Diagnosismentioning
confidence: 99%